Comparison of Performance Evaluation of Grid-Connected PV System for 3D Single Family House Using Building Information Modeling (BIM) Technology: A Case Study in Elazig, Turkey - Homood, Abdiljabbar Rafi; Albarazanch, Salih Habib Najib; Ekici, Sami; Ekici, Betul Bektas (Int Journal Renewable Energy Research, 2020)
In this study, the engineering design of the proposed single family house project was carried out using the well-known architectural program called the Revit that provides a Building Information Modelling (BIM) tool to analyse the falling solar radiation on the specified location. Based on BIM, regions with abundant solar radiation were chosen for the purpose of installing the PV system and exploiting them in energy production. A simulation of a 6.96 KWh grid-connected rooftop PV system was performed by using PVsyst and PV*SOL software. A 3D single family house that was proposed by the municipality of the Turkish city of Elazig was designed and simulated using PVsyst and PV*SOL software based on BIM. Comparison and evaluation were carried out for the annual energy yield, performance ratio, specific production and energy feed into the grid of the PV system from each software. It has been shown that very similar results are obtained from the simulations of these softwares.
Keywords: PV system; solar energy; BIM; PVsyst; PV*SOL; solar radiation